Definition of the early HIV-1 signalosome in dendritic cells - Khatamzas, E (2013)
DCs are critical to the early events of HIV-1 infection. They are the first cells that HIV-1 encounters at mucosal surfaces and as sentinel antigen-presenting cells of the immune system these should alarm the immune system and activate innate immune defences to recruit effective adaptive immunity and viral clearance. A peculiar characteristic of HIV – in contrast to other ssRNA viruses – is its ability to completely evade host innate recognition pathways. Additionally, it has the unique ability to manipulate the endo-lysosomal system of DCs and promote transmission via trans-infection to CD4+ T cells across virological synapses. However, it is largely unknown how HIV-1 is sensed by the innate immune system. Here, a multipronged experimental approach based on phosphoproteomics, transcriptomics and custom RNAi screen was developed to characterize the early signaling complex induced by HIV-1 in DCs. A novel method of phosphoproteomics to identify the HIV-1 phosphoproteome in DCs showed that 342 proteins were differentially phosphorylated following 10 min of HIV-1 infection compared to time-matched mock-infected DCs. Functional analysis of these phosphoproteins showed enrichments in several cellular pathways, including vesicular trafficking, cytoskeletal rearrangements and the secretory pathway and a relative paucity of signaling molecules involved in inflammatory pathways. Proteomics analysis of HIV-1 virions was undertaken to identify host molecules hijacked by HIV-1 during viral replication and revealed a close interaction between the virus and the endo-lysosomal system. Transcriptomics analysis of HIV-1 infected DCs showed a muted immune response with no detectable differentially regulated genes. The results of the phoshoproteomic screen provided the basis for a custom RNAi screen to identify host proteins that are differentially phosphorylated by the virus and required for efficient trans-infection from DCs to CD4+ lymphocytes. The results of this screen showed that 54 of the 120 host factors tested were required for efficient viral transfer to CD4+ T cells and characterize the compartment that HIV-1 is internalized in on a molecular level. Two host factors identified within the HIV-1 phosphoproteome were chosen for further studies. Studies of BLOC-1 (biogenesis of lysosome-related organelles complex-1) and its subunits identified a role for snapin in HIV-1 trans-infection and HIV-1 and TLR8 sensing. Snapin may act as determinant of sorting of HIV-1 intraluminal vesicles to non-degradative, non-immunogenic compartments by activating mammalian target of rapamycin, mTOR, and inhibiting autophagy. Furthermore, HIV-1 triggered dephosphorylation of the cytosolic tyrosine phosphatase possibly via the interaction of host CD47 incorporated in the virion and the transmembrane glycoprotein SIRPα expressed on DCs. Blocking of this interaction with an inhibitory CD47 antibody resulted in a reduction of HIV-1 replication. Taken together, this multipronged approach reveals the complexity of the interaction of HIV-1 with the host cell machinery and identifies novel mechanism of the immune evasion tactics usurped by HIV-1.